Analysis of a Stochastic SIR Model with Vaccination and Nonlinear Incidence Rate - Amine El Koufi; Jihad Adnani; Abdelkrim Bennar; Noura Yousfi (International Journal of Differential Equations)
We expand an SIR epidemic model with vertical and nonlinear incidence rates from a deterministic frame to a stochastic one. The existence of a positive global analytical solution of the proposed stochastic model is shown, and conditions for the extinction and persistence of the disease are established. The presented results are demonstrated by numerical simulations.